Nursing Judgment: A Concept Analysis. (July 2019) - de Tantillo, Lila; De Santis, Joseph P.
Abstract : Charged with making decisions to protect and enhance patient well-being, a nurse relies on nursing judgment to render effective patient care. Nursing judgment is the culmination of education, experience, and insight that allows nurses to execute the best action possible on behalf of patients. This concept analysis uses the Walker and Avant method to demonstrate the role of nursing judgment in assessments and interventions, delegation of tasks, and prioritization of care. Nurses, other health care collaborators, and recipients of health care should be aware of the role played by nursing judgment to improve patient care and the health care system.